Inhibition of Germination and Seedling Growth of Crops by Aqueous Extracts of Shrubs - Rathore, V S; Singh, J P; Beniwal, R K (Annals of Arid Zone, 2016)
The effect of aqueous extracts of arid shrubs viz., Calligonum polygonoides, Haloxyloll salicomicum and seedling growth of Pennisetum americanum, Vigna acollitifolia and Cyamopsis tetragonoloba were investigated. Aqueous extracts of shrubs inhibited germination and seedling growth of all the crops especially at higher concentrations. Inhibitory effect of shrubs on germination and seedling growth was concentration and species specific. Maximum reduction in germination and seedling growth of test crops was caused by H. recurvum followed by H. salicornicum and C. polygonoides. Key words: Allelopathy, shrubs, crops, seedling, vigor, vigor index.